Working with undergraduate students of Translation with a genre-based approach - Paiva, Paula Tavares Pinto (Revista Horizontes de Linguistica Aplicada, 2012)
Research articles in national and international journals provide abstracts usually written in English. This paper discusses the importance of working with this sub-genre with future researchers and translators during their university years. Two concepts of genre are presented (SWALES, 1990; BATHIA, 1993), as well as an approach on how to introduce academic genre to undergraduate students. After applying this approach to a mini-course about academic writing, we have noted that translation students have been more attentive to the way they deal with texts based on communicative purposes, tasks, target readers and language.